If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n = 4 + 5n Solving 3n = 4 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. 3n + -5n = 4 + 5n + -5n Combine like terms: 3n + -5n = -2n -2n = 4 + 5n + -5n Combine like terms: 5n + -5n = 0 -2n = 4 + 0 -2n = 4 Divide each side by '-2'. n = -2 Simplifying n = -2
| -(x-7)+1=7x+8(1-x) | | r-3=12 | | 9v^3-9v=0 | | 19x-(8x-2)=24 | | 2d+23=237 | | 2d+4=256 | | 9x+3=-5 | | 5x-10(x+1)=-5+19 | | (x-8)2=9 | | 43=15-x | | 14x-84=0 | | 3x+9=-2x | | 4x+5=10x | | 5r-15=-12+4r | | 3x+1+4x-3=5x+4 | | -6x+3=5x-129 | | 6n-29=-14+n | | -4x+2(5x-6)=-3(x+13) | | -4x+1=-89+5x | | 5x+20-x+8=2 | | .5(2n+6)=2n-12-n | | x+3=36+4x | | -7x+2=5x+14 | | -3x-12x=-120 | | 9(x+1)-(5x-3)=3 | | 7(10-6x)=58-6(6x+1) | | -8=-7x | | 7(x+3)-(4x-9)=8 | | 4(5+2q)=-4+5q | | -6(-1x+8)=18 | | x^2-50=-1 | | 65-34.3=x |